2015
DOI: 10.1002/glia.22857
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of in vitro endothelial barrier integrity by Japanese encephalitis virus‐Infected astrocytes

Abstract: Blood-brain barrier (BBB) characteristics are induced and maintained by crosstalk between brain microvascular endothelial cells and neighboring cells. Using in vitro cell models, we previously found that a bystander effect was a cause for Japanese encephalitis-associated endothelial barrier disruption. Brain astrocytes, which neighbor BBB endothelial cells, play roles in the maintenance of BBB integrity. By extending the scope of relevant studies, a potential mechanism has been shown that the activation of nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 43 publications
4
89
0
Order By: Relevance
“…Previous studies have revealed that although TBEV infects astrocytes, viral infection did not affect the viability of the cells [34,35]. Similar findings have been observed with other viral infections such as WNV, JEV, and Junin virus whereas infection with Venezuelan equine encephalitis virus infection induced cell death in cultured astrocytes [31,37,39,85,86]. However, the mechanism underlying the resistance to virus-induced cell death in astrocytes is not well understood.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Previous studies have revealed that although TBEV infects astrocytes, viral infection did not affect the viability of the cells [34,35]. Similar findings have been observed with other viral infections such as WNV, JEV, and Junin virus whereas infection with Venezuelan equine encephalitis virus infection induced cell death in cultured astrocytes [31,37,39,85,86]. However, the mechanism underlying the resistance to virus-induced cell death in astrocytes is not well understood.…”
Section: Discussionsupporting
confidence: 65%
“…Both rat and human astrocytes have been shown to be infected in vitro with TBEV; however, the number of infected cells never exceeded 20 %, and the infection did not affect astrocyte viability [34,35]. Similar findings have also been observed for other neurotropic flaviviruses [36][37][38][39]. Therefore, we set out to investigate how the type I IFN system in primary mouse astrocytes contributes to cell survival and restriction of neurotropic flavivirus growth.…”
Section: Introductionsupporting
confidence: 57%
“…143 The polyubiquitination of claudin-5 (Lys-199), ZO-1, Ve-cadherin, JAM-A, cortactin and particularly connexins trigger junction protein proteasome-dependent degradation and serve as a mechanism of protein turnover and junction complex remodeling. 65,[144][145][146][147] So far, the ubiquitination and proteasomal degradation of occludin is the only one described as an underlying mechanism of BBB dysfunction in permanent brain ischemia.…”
Section: Degradation Of Junction Proteins and Bbb Dysfunctionmentioning
confidence: 99%
“…KLF4 has been reported to regulate the endothelial barrier function in glioma cells, by suppressing the promoter activity of tight junction proteins . Further, disruption of BBB has been documented in JEV infection where the tight junction proteins are degraded . Therefore, the suppression of KLF4 during JEV infection and disruption of BBB might be co‐related.…”
Section: Discussionmentioning
confidence: 99%